MORPHOLOGICAL AND PHYSICAL CHARACTERIZATION OF ZAGGA SOILS A SEMI-ARID LANDSCAPE IN NORTHWESTERN NIGERIA - Sharu, Murtala Bawa; Noma, S. S.; Abubakar, G. A.; Eniolorunda, N. B. (FUDMA JOURNAL OF SCIENCES, 2025)
Soils of the Zagga District display strong variability in physical and morphological characteristics, which affect drainage, aeration, and agricultural productivity. Understanding these variations is critical for identifying constraints and recommending sustainable management practices. Soil profiles (ZG6–ZG13) were described morphologically and analyzed for particle size distribution, bulk density, particle density, porosity, gravimetric moisture content, and silt/clay ratio. Descriptive statistics and Pearson correlations were used to evaluate variability and interrelationships among properties. The soil composition was predominantly sand, with an average content of 59.5%, followed by silt at 18.1% and clay at 17.7%. Bulk density averaged 1.78 g cm⁻³, with over half of the profiles exceeding the 1.6 g cm⁻³ threshold for root restriction. Porosity averaged 23.7%, well below the 40–60% considered optimal. Morphological observations confirmed poor drainage in ZG6, ZG7, ZG9, ZG10, and ZG11, while ZG12 and ZG13 were better drained but limited by low water retention. The soils present contrasting limitations, with some profiles prone to waterlogging and others to drought. Site-specific management is essential, including drainage improvements in poorly drained soils and organic matter addition, mulching, and irrigation scheduling in sandy profiles, to enhance productivity and sustainability.
Keywords: Soil morphology; texture; bulk density; Northwestern Nigeria; Pedology